KONSEPSI FITRAH MANUSIA DALAM PERSPEKTIF ISLAM DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM KONTEMPORER - Toni Pransiska (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2016)
One important concept in Islamic education is the concept of Fitrah. The concept of Fitrah is not identical with the Empirism Theory (tabularasa theory). Therefore, the Empirism theory - propounded by John Locke - view that people is white, like the paper has not been crossed out. Environment and education is that gives color to the paper. In contrast, the view that human nature (Fitrah) is more than just a white paper and clean, but in nature there is the potential that is carried by humans. That potential is the power or strength to accept religion or Tauhid. Therefore, the environment and education has a strategic role in developing human nature.Finally, well-educated nature make him as a generation of people who love peace, inclusive and continuous improvement.